Konstytucyjne warunki uczestnictwa w unii walutowej – wybrane zagadnienia - Pawłowski, Szymon (Polski Przegląd Stosunków Międzynarodowych, 2018)
Constitutional conditions for participation in Monetary Union-selected issues This article discusses the changes in the constitutional regulation of Member States concerning the monetary union. Analysis have been subjected to the ECB'S recommendation concerning the need for amendment of the Constitution, in the context of the preparation of the convergence with condition of the accede to the monetary union, and the options of the new constitutional regulation after Poland entry to the eurozone. Discussed was also the issue of NBP'S authorities in the context of the participation of the Polish Central Bank into the ESCB.